PENGARUH STRUKTUR AKTIVA DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR BARANG KONSUMSI DI BURSA EFEK INDONESIA TAHUN 2016-2018 - Armita, Luh Ayu; Indraswarawati, Sang Ayu Putu Arie (Hita Akuntansi dan Keuangan, 2020)
Thel purpose ofl thisl study was to determine thel effect ofl assetl structurel and company size onl capital structurel inl thel manufacturingl companies inl thel consumer goods industry sector which were listed onl thel Indonesial Stock Exchange inl 2016-2018. Thisl study uses external secondary data, external secondary datal used inl thisl study is thel annual report ofl thel consumer goods industry sector which is onl thel Indonesial Stock Exchange inl 2016-2018 through thel website www.idx.co.id. inl thisl study thel samplingl usingl Purposive Samplingl techniques with certain considerations, where thel sample is 72 companies manufacturingl consumer goods industry sectors which are listed onl thel Indonesial Stock Exchange inl 2016-2018. Thel datal analysis technique used is multiple linearl regression analysis. Based onl thel results ofl thel analysis found that assetl structurel has a positive and significant effect onl capital structurel. Thisl shows that increasingl thel structurel ofl assetls inl companies manufacturingl consumer goods, it tends to increase thel capital structurel. Thel size ofl thel company has no significant effect onl capital structurel. Thisl shows that changes inl company size (up or down) inl consumer goods manufacturingl companies, do not affect thel capital structurel.